A case study of multimodal and authoritative meaning making in grade 5 isiZulu, English, and Natural Sciences lessons in a quintile 1 primary school - Msimango, Mfundo Jabulani (School of Education, 2023)
This is a case study of multimodal and authoritative meaning making in grade 5 isiZulu, English, and Natural Sciences lessons in a quintile 1 primary school in KwaZulu-Natal, uMzinyathi Municipality in Nqutu. This study investigated the nature of classroom discourse in each of the subject areas and the opportunities learners have for participation in multimodal classroom discourse. This study is grounded in the socio-cultural approach, language and literacy as a social practice, and multimodality. Furthermore, this study adopted case study, and linguistic ethnography as a methodology. There are three major findings. First multimodality is not inherently pedagogically transformative, its success is determined by how multimodality is used, and integrated with the educator's pedagogy. Second, the presence and the use of multimodality and translanguaging does not compensate for monolingual assessments. That is, even though the isiZulu, English, and natural sciences educators were translanguaging and employing multiple modes of communication in the classroom, the written discourse was strictly monolingual in isiZulu/English. For example, learners were expected to write isiZulu class activities in monolingual isiZulu, and to write English and natural class activities in monolingual English, following bilingual oral classroom talk. Last, there is a similar communicative pattern across isiZulu, English, and natural sciences lessons. That is, the educators' pedagogical discourse was authoritative and interactional to a limited extent even in the isiZulu lessons where most learners are believed to be speaking isiZulu as their home language. In connection to this, knowledge and multimodal artefacts are presented as fixed, and learners are not given an opportunity to engage them fully nor to question, even in the isiZulu lessons where the language of instruction correlates with most learner's home language.